Questioning the Universality of Institutional Transformation Theories in Spatial Planning: Shopping Mall Developments in Palermo - Tulumello, Simone (2016)
Theories about institutional transformation in spatial planning, although mainly based on the Anglo-Saxon context, have assumed a dominant role in planning research and theory as means to understand the transformations that have been restructuring planning systems in recent decades in the Western world and beyond. The article, looking at transformations of planning practice through the lenses of the concept of planning cultures, debates the utility of building ‘universal’ theories for spatial planning and advocates for the need for a de-provincialization of planning theories. This is done through a case-study approach applied to the history of the transformation of the retail system in a context characterized by the specificities of the Italian planning context and Southern European cities, namely: the planning processes for, and power relationships underlying, the first shopping malls opened in Palermo, Italy, since 2009 — some decades later than most of Western cities.